The Effect Of Work Discipline And Working Hours On The Performance Of PPPK Employees At The Fire Department Of South Bengkulu Regency - Andriani, Delvi; Anggriani , Ida; Ariantara, Yudi (Universitas Dehasen Bengkulu, 2024)
Human resources have a very strategic position in the organization, meaning that the human element plays an important role in carrying out activities to achieve goals. The purpose of this study was to determine the effect of Work Discipline and Working Hours on the performance of PPPK employees at the South Bengkulu Regency Fire Service. This type of research uses quantitative research. The analysis method in this study uses the Validity test, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient, Classical Assumption Test and hypothesis testing using the t test. The number of samples studied was 35 PPPK Firefighters. The results of the multiple linear regression analysis are Y = 11.756 + 0.343 X1 + 0.389 X2 + e, this illustrates the positive direction of regression, meaning that the work discipline variable (X1) and work discipline (X2) have a positive influence on employee performance (Y) at Damkar South Bengkulu Regency. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination of R square is 0.688. This means that the value of work discipline (X1) and the value of working hours (X2) affect employee performance (Y) by 68.8% while the remaining 31.2% is influenced by other variables not examined in the study.